Monte Carlo GEANT4-based application for in vivo RBE study using small animals at LNS-INFN preclinical hadrontherapy facility - Pisciotta, P.; Cammarata, F.P.; Stefano, A.; Romano, F.; Marchese, V.; Torrisi, F.; Forte, G.I.; Cella, L.; Cirrone, G.A.P.; Petringa, G.; Gilardi, M.C.; Cuttone, G.; et al. (Physica medica, 2018)
•The relative biological effectiveness along Bragg peak is not constant.•Our GEANT4application uses DICOM images to define target.•A GEANT4application to support future RBEin vivostudies was developed.•The mean linear energy transfer of each treatment configurations was studied.•Our approach is a good way to improve radiation protocols in animal science. Preclinical studies represent an important step towards a deep understanding of the biological response to ionizing radiations. The effectiveness of proton therapy is higher than photons and, for clinical purposes, a fixed value of 1.1 is used for the relative biological effectiveness (RBE) of protons considered 1.1. Recent in vitro studies have reported that the RBE along the spread-out Bragg peak (SOBP) is not constant and, in particular, the RBE value increases on the distal part of SOBP. The present work has been carried-out in the perspective of a preclinical hadrontherapy facility at LNS-INFN and was focused on the experimental preparation of an in vivo study concerning the RBE variation along the SOBP. The main purpose of this work was to determine, using GEANT4-based Monte Carlo simulations, the best configuration for small animal treatments. The developed GEANT4 application simulates the proton-therapy beam line of LNS-INFN (CATANA facility) and allows to import the DICOM-CT images as targets. The RBE will be evaluated using a deterministic radiation damage like myelopathy as end-point. In fact, the dose at which the 50% of animals will show the myelopathy is supposed to be LET-dependent. In this work, we studied different treatment configurations in order to choose the best two that maximize the LET difference reducing as much as possible the dose released to healthy tissue. The results will be useful to plan hadrontherapy treatments for preclinical in vivo studies and, in particular, for the future in vivo RBE studies.